Improving the English-speaking skills of tourists in Wonocoyo village through bilingual guidebook - Dwi Wahyuningtyas; Laksmi Diana; Rina Wahyu Setyaningrum; Revina Dwi Masayu; Adinda Deviana; Yustin Dwi Rahmawati (Universitas Muhammadiyah Malang, 2024)
Through this research, the researchers intended to seek information and data on how a bilingual guidebook improves the tour guides' speaking skills. This research provides an overview of classroom action research conducted in Wonocoyo Tourism village to investigate their improvement in English skills using a bilingual guidebook the researcher designed. The research participants were four tour guides in Desa Wisata Wonocoyo Panggul, Trenggalek. They were given a pretest and two post-tests to observe their pretest skills deposit tests. The pretest showed that the English skills level of the tour guides was low to intermediate. The treatment was then given using the bilingual guidebook designed for the post-test. The researcher designed the planning, action, observation, and reflection that become the fundamentals of two post-tests. The first post-test indicated good results, and the tour guides experienced improvement in some aspects. After some reflection, the researcher conducted the second post-test, resulting in a better score for the tour guides. The result revealed that the English skills of the tour guide English skills, mainly speaking, can be improved through the bilingual guidebook.